Animal experimental evaluation of a new sealing device for indwelling arterial catheters. (June 2013) - Isfort, Peter; Urban, Ute; Mahnken, Andreas Horst; Penzkofer, Tobias; Bruners, Philipp; Pfeffer, Joachim; Steinseifer, Ulrich; Günther, Rolf Wilhelm; Schmitz-Rode, Thomas
Background: Hematoma is a common complication following arterial puncture. To date no device that allows sealing of an arterial puncture site with in-situ catheter has been developed. Purpose: To evaluate a newly developed arterial sealing device for endovascular catheters in an in-vivo experimental setting. Material and Methods: A peelable collagen-based vascular sealing device for endovascular catheters was tested in acute (follow-up: 4 h; n = 2) and chronic (follow-up: 1 week; n = 4) settings in the femoral artery (FA) of sheep. After implantation correct position of the device as well as patency of the FA were verified angiographically. In the chronic group, hematoma was excluded and patency of FA was assured using color Doppler ultrasound 1 and 3 days after the procedure. After 1 week a final ultrasound and an angiography were performed for final evaluation. Thereafter, the animals were sacrificed and the puncture site was dissected and analyzed macroscopically. Results: Sufficient sealing of the puncture site could be observed in all animals. In acute and chronic experiments, neither a hematoma at the puncture site nor other complications were observed after positioning the sealing device. Follow-up color Doppler ultrasounds (CDUS) and final angiography revealed patent FAs in all animals. Macroscopic evaluation of dissection material proved collagen plug and catheter being in place. Conclusion: Our preliminary in-vivo results demonstrate a safe and convenient vascular sealing system for endovascular catheters. No acute or chronic complications were observed.